Long Patch Base Excision Repair Proceeds via Coordinated Stimulation of the Multienzyme DNA Repair Complex - Balakrishnan, Lata (American Society for Biochemistry and Molecular Biology, 2009)
Base excision repair, a major repair pathway in mammalian cells, is responsible for correcting DNA base damage and maintaining genomic integrity. Recent reports show that the Rad9-Rad1-Hus1 complex (9-1-1) stimulates enzymes proposed to perform a long patch-base excision repair sub-pathway (LP-BER), including DNA glycosylases, apurinic/apyrimidinic endonuclease 1 (APE1), DNA polymerase β (pol β), flap endonuclease 1 (FEN1), and DNA ligase I (LigI). However, 9-1-1 was found to produce minimal stimulation of FEN1 and LigI in the context of a complete reconstitution of LP-BER. We show here that pol β is a robust stimulator of FEN1 and a moderate stimulator of LigI. Apparently, there is a maximum possible stimulation of these two proteins such that after responding to pol β or another protein in the repair complex, only a small additional response to 9-1-1 is allowed. The 9-1-1 sliding clamp structure must serve primarily to coordinate enzyme actions rather than enhancing rate. Significantly, stimulation by the polymerase involves interaction of primer terminus-bound pol β with FEN1 and LigI. This observation provides compelling evidence that the proposed LP-BER pathway is actually employed in cells. Moreover, this pathway has been proposed to function by sequential enzyme actions in a “hit and run” mechanism. Our results imply that this mechanism is still carried out, but in the context of a multienzyme complex that remains structurally intact during the repair process.